Cadherin selectivity filter regulates endothelial sieving properties - Quadri, Sadiqa K. (2012)
The molecular basis of endothelial protein sieving, the critical vascular barrier function that restricts flow of large plasma proteins into tissues while allowing small molecules and water to pass, is not understood. Here, we address this issue using a novel assay to detect macromolecular penetrance at microdomains of endothelial adherens junctions. Adherens junctions, as detected by cadherin-GFP expression, were distributed in the cell perimeter as high- or low-density segments. Low but not high-density segments permitted penetrance of a 70-kDa fluorescent dextran, a molecule of equivalent size to albumin. Expression of a cadherin mutant that abrogates strand–swap adhesive binding in the cadherin EC1 ectodomain, or alternatively of an α-actinin-1 mutant that inhibits F-actin bundling, increased both cadherin mobility and 70 kDa dextran penetrance at high-density segments. These findings suggest that adhesive interactions in the cadherin EC1 domain, which underlie adherens junction structure, are critical determinants of endothelial macromolecular sieving.